2019
DOI: 10.1016/j.soard.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant activity of enoxaparin and unfractionated heparin for venous thromboembolism prophylaxis in obese patients undergoing sleeve gastrectomy

Abstract: Background: One risk of bariatric surgery is venous thromboembolism and the optimal strategy to reduce risk requires further clarification. Objectives: The objectives of this study were to identify antiXa goal attainment with the institutional standard chemoprophylaxis, analyze discordance between antiXa and thrombin generation assay (TGA) in terms of adequacy of anticoagulation, and to identify correlations between patient characteristics or covariates and markers of coagulation status. Setting: Large academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Overall, the five prospective cohort studies on enoxaparin included a low number of obese patients (n ¼ 39-223), and, if any, only a few cases of VTE and bleedings were observed. [9][10][11][12][13] Therefore, their conclusions mainly relied on biochemical measures. Three studies, collectively, seemed to agree on the notion that 40 mg once or twice daily is associated with a relatively low proportion of patients reaching the biochemical target, especially in patients > 150 kg.…”
Section: Prophylaxis In Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the five prospective cohort studies on enoxaparin included a low number of obese patients (n ¼ 39-223), and, if any, only a few cases of VTE and bleedings were observed. [9][10][11][12][13] Therefore, their conclusions mainly relied on biochemical measures. Three studies, collectively, seemed to agree on the notion that 40 mg once or twice daily is associated with a relatively low proportion of patients reaching the biochemical target, especially in patients > 150 kg.…”
Section: Prophylaxis In Bariatric Surgerymentioning
confidence: 99%
“…9-11 However, Brunetti et al did observe that 40 mg twice daily was sufficient in the majority of patients, but a wider anti-Xa range of 0.1 to 0.5 IU/mL was utilized in this study. 12 The largest prospective study by Borkgren-Okonek et al included 223 patients and found satisfactory anti-Xa levels and only a single VTE event with enoxaparin 40 mg twice daily during hospitalization, followed by 40 mg once daily for 10 days after discharge for patients with BMI 50 kg/m 2 and 60 mg once daily for patients with BMI > 50 kg/m 2 . 13 Nine retrospective studies, based on medical chart review, evaluating enoxaparin, were found.…”
Section: Prophylaxis In Bariatric Surgerymentioning
confidence: 99%
“…Many previous studies have tested different dosages of enoxaparin for patients with obesity [ 12 14 , 19 , 23 , 24 ]. Most of them focused on the optimal dosage regimen while not taking sex into account.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-factor Xa activity was measured 4-5 h after enoxaparin application on the third day after surgery. An anti-factor Xa activity between 0.1 and 0.4 U/mL was chosen as the target range for thromboprophylaxis, according to the literature [15][16][17][18][19] and our local laboratory values. The anti-factor Xa assay quantitatively measures the amount of factor Xa left in the sample in a chromogenic assay and is inversely proportional to the amount of LMWH [6].…”
Section: Patient Selectionmentioning
confidence: 99%
“…Анти-Xa активность -это лабораторный показатель, отражающий противосвертывающую активность НМГ. Данные исследований, проведенных у пациентов, получающих профилактические дозировки НМГ, лабораторный контроль которых осуществлялся с помощью данного метода, оказались противоречивы [13][14][15].…”
Section: Discussionunclassified